O périplo do espanto: as manifestações do sujeito lírico na poesia de Ferreira Gullar - Giani, Guilherme Bruno (2023)
The purpose of this dissertation is to investigate the manifestations of the lyrical subject in Ferreira Gullar's poetry. The general hypothesis is that the multiplicity of expressions of the poet stems from a conception of poetic creation as an ontological-aesthetic exercise, in a quest to invent himself in the world through writing. Thus, to follow the expressive directions of this lyrical voice is to decipher how it conceives, throughout the books, the process of constitution of its identity in the world. To this end, we divide the work into five chapters: in the first, we elucidate basic questions of modern poetry in order to investigate the lyric subject; then, in the remaining four chapters, we trace a chronological path through Gullar's poetry by analyzing a diversity of poems, either whole or in excerpts, aiming to understand the process of constitution of the lyric voice in each phase of the work. In the second chapter, we trace the first steps taken by the subject, afflicted by frustration with the impossibility of transcendence through poetry and, therefore, constituted by a desolate consciousness and a split identity. In the next chapter, we elucidate the paradigmatic turn in Gullar's poetry, which reconfigures the subject in a concrete and social setting, giving him his status as a common man, muddy and dirty. Then, in the third chapter, we follow the subject's expressive maturation into an autobiographical feature that purifies colloquialism into a concise and contained diction, characterizing the art of translation. Finally, we investigate the last phase of the poet's work - which, for being recent, has a smaller critical fortune, which encouraged us to broaden the analysis - where we find the constant concern with death acquiring less rapture, and the subject,despite being rooted in a deep colloquial and autobiographical root, consolidates a firm and acute reflection on his end, which works as an empirical/aesthetic knot in his work/life. The methodology of the research is bibliographic, and consists, fundamentally, in reading the complete poetic work of Ferreira Gullar, present in Toda poesia (2015), which brings together all the books of the author: A luta corporal (1954), O vil metal (1960), Dentro da noite veloz (1974), Poema sujo (1976), Na vertigem do dia (1980), Barulhos (1987), Muitas vozes (1999), and Em algum parte alguma parte (2010). In addition, we also read other texts by Gullar (essays, memoirs, interviews), part of the robust critical fortune produced about him – notably, João Luiz Lafetá (2004), Alcides Villaça (2017), Alfredo Bosi (2016), Eleonora Camenietzki (2006) and Viviana Bosi (2017) – and some fundamental texts on modern poetry, especially on lyric subject – Kate Hamburger (2013), Dominique Combe (2010) and Michel Collot (2013)